Internet Diffusion and Government Intervention: The Parody of Sustainable Development in Africa. - Bidemi, G. Badmus (Journal of Pan African Studies, 2017)
This paper argues that the current attacks on Internet access in terms of legal constraints, political intimation, Internet shutdown, unlawful arrest of Internet users, and the purposeful disruption of Internet services by government agents will become more pronounced unless African nations technologically develop public institutions to compete constructively with private Internet service providers, in terms of information communication. The data utilized for this study were basically sourced from secondary data collection, and thus contently analyzed based on the nature and practical experience of how the access and the use of Internet has been hindered through undue intervention by governments in Africa. The paper also outlines a set of recommendations for improvement.